Measurement of Self-Reported Physical Activity with Cardiovascular Risk in Rural Adults in Jombang District, East Java Province - Syahrul, Fariani; Adi, Annis Catur; Anisah, Mufidah; Dewi, Ratna Candra (Universitas Aisyah Pringsewu, 2024)
Cardiovascular disease (CVD) was the leading cause of death globally in 2019. The risk of CVD include cholesterol and blood sugar levels, blood pressure, and Body Mass Index (BMI). Physical activity is one of the protective factors of cardiovascular disease. This study aims to analyze measurement of self-reported physical activity with cardiovascular risk in rural adults in Indonesia. This study was an observational analytic with a cross-sectional design. All adults (aged 12-59 years) about 93 samples were obtained using an accidental sampling technique. Collecting data involves assessing physical activity using the Global Physical Activity Questionnaire (GPAQ) and cardiovascular risk was calculated using the Framingham 30-Year Risk Score. The data were analyzed using the Spearman test. The majority of respondents were female (52.7%), in the late adult age category (83.9%), high school graduate (51.6%), an employee (64%), and income of respondents (33.3%) were Rp 2.000.000. Physical activity was associated with cardiovascular risk physical activity had a higher risk of cardiovascular disease and vice versa. Physical activity does not correlate with CVD risk factors, such as cholesterol levels, blood sugar levels, BMI, and blood pressure among adults in rural areas in Jombang, Indonesia. Measurement of self-reported physical activity can increase cardiovascular risk in rural adults in Indonesia. A healthy lifestyle by increasing physical activity should be carried out in adulthood to prevent the risk of cardiovascular disease.